2014
DOI: 10.1177/0731121414534393
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Motherhood and Fertility Intentions among U.S. Women

Abstract: Fertility intentions are associated with achieved fertility; therefore, understanding the factors associated with fertility intentions is important. Considerable research has examined factors associated with fertility intentions, but no one has explored the importance of motherhood to women. Guided by life course and identity theories, we use the National Survey of Fertility Barriers, a data set collected from a random sample of U.S. women aged 25-45 in 2004 through 2007, to assess the relationship between imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…Research supporting the importance of prior reproductive experiences/contexts for subsequent reproductive behaviors and attitudes [17] led to the inclusion of age at first pregnancy (in years) and outcome of the first pregnancy (live birth, pregnancy loss, and abortion), which were included as dichotomous variables. In addition to measures of reproductive context, we included measures economic/social status and values/ideologies, both of which have been linked to pregnancy intentions in prior studies utilizing the NSFB [11,18]. The economic/social characteristics we included were union status, economic hardship, race/ethnicity, and work status.…”
Section: Datamentioning
confidence: 99%
“…Research supporting the importance of prior reproductive experiences/contexts for subsequent reproductive behaviors and attitudes [17] led to the inclusion of age at first pregnancy (in years) and outcome of the first pregnancy (live birth, pregnancy loss, and abortion), which were included as dichotomous variables. In addition to measures of reproductive context, we included measures economic/social status and values/ideologies, both of which have been linked to pregnancy intentions in prior studies utilizing the NSFB [11,18]. The economic/social characteristics we included were union status, economic hardship, race/ethnicity, and work status.…”
Section: Datamentioning
confidence: 99%
“…Fertility intentions can tell us the extent to which this double negative effect of education on fertility is intentional, or is instead the outcome of fertility plans that are not realised. The prediction made in the literature on the second demographic transition that ideational change lowers people's fertility intentions by emphasising individuals' self-realisation needs and values (Van de Kaa 2002;Caltabiano et al 2009;Lesthaeghe 2010;McQuillan et al 2014) has not come true. Post-materialist attitudes do not seem to be negatively correlated with ideal family size, and a considerable number of studies have found that fertility intentions are indeed higher among highly educated than among less educated women (De Wachter and Neels 2011;Mills et al 2008;Roukolainen and Notkola 2002); and that these intentions are often closely clustered around the level of two children (Testa 2014).…”
Section: The Role Of Education In Fertility and Reproductive Decisionmentioning
confidence: 99%
“…However, the link between education and fertility intentions may also turn from negative to positive over the life course when specific birth order intentions come into play. Intentions decline with the birth of each additional child (McQuillan 2014;Liefbroer 2009), but they may decrease less among highly educated women and men who can afford to have a larger family than among less educated women and men who cannot.…”
Section: The Role Of Education In Fertility and Reproductive Decisionmentioning
confidence: 99%
“…This figure has remained relatively stable for two decades and has inspired researchers to study topics such as the determinants of fertility intentions (McQuilan, Greil, Shreffler et al ., 2015; Reed and Mcbroom, 1995; Gatny, Kusunoki, and Barber, 2014), which groups of women are more likely to experience an unintended pregnancy (Finer and Zolna, 2014; Finer and Henshaw, 2006), to what extent individuals fulfill their desired family size (Berrington and Pattaro, 2014; Hartnett, 2014; Morgan and Rackin, 2010; Miller, Rodgers, and Pasta, 2010), and how well their intentions to have children within a specified time period are met (Miller, Rodgers, and Pasta, 2010; Heaton, Jacobson, and Holland, 1999; White and McQuilan, 2006). However, only a handful of studies have used longitudinal data to examine other fertility and family planning behaviors (Jones, Tapales, Lindberg et al , 2015).…”
Section: Introductionmentioning
confidence: 99%